Rhetoric of a global epidemic : transcultural communication about SARS - Ding, Huiling (Southern Illinois University Press, 2014)
In the past ten years, we have seen great changes in the ways government organizations and media respond to and report on emerging global epidemics. The first outbreak to garner such attention was SARS (severe acute respiratory syndrome). In Rhetoric of a Global Epidemic, Huiling Ding uses SARS to explore how various cultures and communities made sense of the epidemic and communicated about it. She also investigates the way knowledge production and legitimation operate in global epidemics, the roles that professionals and professional communicators, as well as individual citizens, play in the.